From marketising to empowering: Evaluating union responses to devolutionary policies in education. (March 2022) - Gavin, Mihajla; Fitzgerald, Scott; McGrath-Champ, Susan
Major reforms in education, globally, have focused on increased accountability and devolution of responsibility to the local school level to improve the efficiency and quality of education. While emerging research is considering implications of these changed governance arrangements at both a school and system level, little attention has been afforded to teacher union responses to devolutionary reform, despite teaching being a highly union-organised profession and the endurance of decentralising-style reforms in education for over 40 years. Drawing upon a power resources approach, this article examines union responses in cases of devolutionary reform in a populous Australian state. Through analysing evolving policy discourse, from anti-bureaucratic, managerialising rhetoric to a 'post-bureaucratic, empowerment' agenda, this article contributes to understandings of union power for resisting decentralising, neoliberal policy agendas by exposing the limits of public sector unions mobilising traditional power resources and arguing for strengthening of discursive and symbolic power. JEL Code: J5